FEATURES AND REGULARITIES OF THE IMPACT OF TAX AVOIDANCE/EVASION SCHEMES ON THE GLOBAL FINANCIAL SYSTEM - Korovchuk , Yu.I.; Kotyk , Kh.R.; Onyshchuk , S.V. (The actual problems of regional economy development, 2025)
The aim of this study is to examine the regularities of the impact of tax avoidance and evasion schemes on the financial systems of countries within the global economic environment. The research employs methods such as analysis and synthesis to generalize approaches to defining tax avoidance/evasion, identifying their forms, characteristics, and consequences; comparative analysis of international practices; and classification of tax avoidance/evasion schemes. The article explores the essential features of modern tax avoidance/evasion schemes, the mechanisms of their implementation, and international experience in counteracting them. It analyzes their classification types, preconditions, models of implementation, and evolutionary traits. The study also models the patterns of influence that tax avoidance/evasion schemes have on the capacity of national financial systems within the global economic context. Based on the research findings, it was concluded that accumulated and paid taxes represent, for the state, resources through which it can ensure its functioning, maintain the social sphere, finance defense, infrastructure, etc. However, from the perspective of taxpayers, taxes essentially constitute a loss of resources that could otherwise be consumed by each individual according to their own needs. It is noted that the spread and intensification of such schemes significantly transform the curve of financial resources by substantially reducing state budget revenues, while the level of maximum profit remains unchanged. Depending on the nature of a country's fiscal policy, the negative effects of tax evasion/avoidance schemes may vary. For countries with high social spending, the loss of revenues will be especially noticeable, while the income growth of other economic agents will be significant. In light of this, the authors suggest that an effective way to optimize a wide range of tax avoidance/evasion schemes could be to deepen fiscal cooperation between countries, particularly in exchanging asset declaration data and introducing a global mechanism for indirect taxation—especially on high-value and luxury goods. These measures would contribute to financial system stability and a fairer distribution of income, although their implementation is extremely challenging due to resistance from elites who benefit from such schemes.